1996
DOI: 10.1021/ja954122g
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl Lewis x Liposomes as a Multivalent Ligand and Inhibitor of E-Selectin Mediated Cellular Adhesion

Abstract: A sialyl Lewis x−PEG−DSPE derivative (3) has been prepared using a combined chemical enzymatic approach and incorporated into mPEG−DSPE containing liposomes (PEG, poly(ethylene glycol); mPEG, methoxypoly(ethylene glycol); DSPE, distearoylphosphatidylethanolamine). Several liposomal formulations of 3 were evaluated as inhibitors of E-selectin mediated cellular adhesion in an ELISA assay and were found to be ∼750-fold more potent than the nonliposomal oligosaccharide (2) and greater than 5000-fold more potent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 22 publications
0
70
0
1
Order By: Relevance
“…Carbohydrate-protein binding events usually involve several simultaneous contacts between carbohydrates that are clustered on cell surfaces and protein receptors that contain multiple carbohydrate-binding sites. Numerous studies on model systems have demonstrated that polyvalent displays of carbohydrates can lead to remarkably high binding avidities (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Because avidity and specificity are not necessarily correlated (6,7), however, polyvalency does not completely resolve the paradox of how marginally selective carbohydrate-binding interactions can produce highly specific responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate-protein binding events usually involve several simultaneous contacts between carbohydrates that are clustered on cell surfaces and protein receptors that contain multiple carbohydrate-binding sites. Numerous studies on model systems have demonstrated that polyvalent displays of carbohydrates can lead to remarkably high binding avidities (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Because avidity and specificity are not necessarily correlated (6,7), however, polyvalency does not completely resolve the paradox of how marginally selective carbohydrate-binding interactions can produce highly specific responses.…”
mentioning
confidence: 99%
“…Simplified model systems are usually used to study polyvalent carbohydrate-protein interactions (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). We recently demonstrated that carbohydrates presented on TentaGel beads exhibit polyvalent binding and may therefore be useful as model systems to investigate the interactions of carbohydrates on surfaces (6, 7).…”
mentioning
confidence: 99%
“…In the natural form, Lewis antigens are attached through their reducing ends to lipids and/or proteins. If Lewis antigen conjugates have the lipids attached to the 2-amino group of the glucosamine residue with the reducing end capped by an unreactive group [38], it may affect the conformation of the antigen and their binding to selectins. Therefore, SuLe a -containing glycolipids 1a and 1b with the lipid moiety at the saccharide reducing end have the advantage of stability under physiological conditions.…”
Section: Synthesis Of Sule a -And Tsule A -Lipidsmentioning
confidence: 99%
“…They bind E-, P-and L-selectin receptors present on activated endothelial cells, platelets and leukocytes during the inflammation process [33][34][35][36]. Therefore, much effort has been focused on the development of new therapeutic strategies for inflamatory diseases, based on using SLe x/a ligands and their analogs [37][38][39][40]. To explore this approach, we have synthesized a natural Lewis type saccharide ligand, 3'-sulfoLewis a (SuLe a ), as well as its glycolipids, and incorporated them into liposomes for targeting P-selectin expressed on activated platelets [41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both polymeric and liposome-like SLex derivatives have been shown to be much more active (by a factor of '70-5000, depending on the structure and formulation) than the monomeric species as inhibitors of E-selectin (57,96,97). The mimetics perhaps can be converted to the multivalent form to increase the activity.…”
Section: Chemoenzymatic Approaches To the Synthesis Of Complex Carbohmentioning
confidence: 99%